PENGHARUM RUANGAN OTOMATIS BERBASIS MIKROKONTROLER ATMEGA 16 - , MAWAR M, Alif Subardono, S.T.,M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In the final project report will be discussed on a microcontroller-based control circuit for controlling the spraying air freshener. The series was created to improve the effectiveness and efficiency of the air freshener. Therefore, it is equipped with air freshener filtur mode selection. Itâs also equipped with a LCD viewer, microcontroller ATMega 16 as a data processor, dc motors as the trigger spraying, RTC as a comparison with the actual time and allotted time, PIR as a sensor to determine whether there is human, and photodiode as a light sensor. There are 3 modes in this automatic air freshener, such as mode 1 is used 3 sensors, mode 2 is used 2 sensors and mode 3 is used 1 sensor.